Mesothelioma diagnosis and prognosis, are we moving beyond histology and performance status towards circulating biomarkers? - Røe, Oluf Dimitri (Journal of Thoracic Disease; Vol 10, Supplement 17 (June 20, 2018): Journal of Thoracic Disease, 2018)
An interesting overview and discussion of which circulating mesothelioma biomarkers are, and which may become clinically relevant, is presented by Huan H. Sun, Allen Vaynblat and Harvey I. Pass in “Diagnosis and prognosis—review of biomarkers for mesothelioma” (1).